The Effect of Problem Based Learning to Improve Student’s Speaking Ability on English Education Program STKIP Kieraha Ternate - Yesri Anti Warsito (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2018)
Yesri Anti Warsito. 2018. The effect of Problem Based Learning to improve students’ speaking ability on English education program at STKIP Kie Raha Ternate. A final project of English education program, College of Teacher Training and Education Kie Raha Ternate. Advisor I. Zainurrahman, S.S, M.Pd and Advisor II. Suhaimi Tegamuni, S.S, M.Pd. The purpose of this study was to investigate the effect of problem based learning in improving students speaking ability. The present study attempted to answer the following question: What is the effect of problem based learning in improving students speaking ability ? The study was an quasy experiment with non-equivalent control group design.The participant in the study was 37 students, that is divided in two part there are experimental and control group. In collecting the data, the researcher used test, interview and documentasi. The researcher conducted the test before (pre-test) and after (post-test). The mean score of each test between experiment and control group was compared to know the students’ in speaking skill. The research result show there is significant difference of students’ speaking ability. The mean score of pre-test in experimental group was 24.62, result of pre-test in control group was 26.07, the post-test in experimental group was 24.69 and the post-test of control group was 26.62. It proved when they learned with problem based learning. They got better scores in post-test.